Production of conjugated linoleic acid by lactic acid bacteria screening and optimization - Tapia, Angelo M.; Oliveros, Maria Cynthia R.; Sarmago, Ione G.; Pham, Laura J.; Mendoza, Bernadette C.; Bautista, Jose Arceo N. (2019)
This study was conducted to screen and optimize locally isolated lactic acid bacteria (LABs) for conjugated linoleic acid (CLA) production. Ten (10) LAB strains were evaluated for CLA production in De Man, Rogosa, and Sharpe (MRS) broth supplemented with 0.01% free linoleic acid (LA). Lipids were extracted from the broth with chloroform/methanol. The resultant fatty acid methyl esters were further extracted with n-hexane and were analyzed by gas chromatography using a Shimadzu GC-14 unit (Shimadzu Corp., Kyoto Japan) equipped with SUPELCOWAX 10 column. Three (3) LAB strains ? Lactobacillus plantarum 1066, Lactobacillus fermentum 1014, and Lactobacillus casei 1064 ? were able to produce CLA. L. plantarum 1066 was selected for optimization where LA supplementation (100 and 200 µg/ml) and incubation time (0, 6, 12, 18, and 24 h) were used as variable factors for CLA production. Supplementation with LA at 100 or 200 µg/ml in MRS broth did not significantly affect the growth of L. plantarum 1066 after 24 h of incubation, as well as its production of CLA. However, it was observed that CLA production showed a strong positive correlation with LA concentration. (Author's abstract)